FACTORS DETERMINING EFFECTIVENESS IN MALAYSIAN SMALL & MEDIUM ENTERPRISES BY IMPLEMENTING GLOBALIZATION STRATEGY - Vorobyova, Kateryna; Raju, Valliappan (PEOPLE: International Journal of Social Sciences, 2017)
This research paper aims at identifying the current issues of Malaysian Small & Medium Enterprises (SMEs) to globalize to enter into new market, identifying companies’ internal and external barriers, identifying gaps of effective global strategy etc. The seriousness of the study will affix the current knowledge of business situation of effective globalization strategy to progress Malaysian SMEs. Earlier there is a study that has been placed that organizes Malaysia SMEs challenges across discipline for a better perspective to unleash SMEs potentials. In particular, benefaction of the SMEs will be creating employment possibility and providing constant economic development in both ways, enlarging entrepreneurial foundation and expanding human capital. With the implementation of the New Economic Policy (NEP) in 1971 which aimed to improve people’s welfare and restructure ethnic, economic imbalances, this step has been shown the importance of SMEs in Malaysia which can be traced back to the early 1970s. The commitment of Malaysian Governments to develop SMEs was further strengthened by the implementation of the Malaysia Industrial Master Plan, particularly the Industrial Master Plan 2 or IMP2 from 2000 to 2005 which was followed by the IMP3 spanning 2006 to 2020. Among other policies, this plan coincides with the country’s vision to be a developed nation by 2020 (MITI, 2005). In this research paper there shall be a significant study on identifying the barriers to globalize and extend the borders for Small & Medium Enterprises (SMEs).